Experimental Study on Vibration Absorption Performance of Floating Slabs of Vibration Isolation Pads in Metro Shield Tunnels. Issue 1 (1st January 2022) - Peng, Guangzhao; Fu, Kun; Zhang, Fengdong; Bai, Jian; Zeng, Zhiping; Li, Zhuang; Yin, Huatuo; Huang, Zhibin; Tang, Qihui
Abstract: The monolithic track bed with isolated damping pad and floating slab is a common design of urban subways in recent years.The type of track bed, urban subway lines usually pass through densely populated areas of the city, and subway trains.In the course of driving, it is inevitable that large track vibration noise will be produced. In order to reduce the impact of track vibration noise on the daily life of surrounding residents, noise reduction measures must be considered during track design. Isolated shock absorber floating board The monolithic track bed is one of them. Compared with the steel spring floating slab monolithic track bed, it has the technical characteristics of "low engineering cost, more convenient construction, and good noise reduction effect". In order to study its damping effect, we selected two working conditions of straight line and curve for comparison. It can be seen from the comparison results with the ordinary track bed: (1) The acceleration level of the shock-absorbing cushion tunnel wall in the straight section is greater than the ordinary track bed section within 1∼10Hz, and is close to the ordinary track bed section within 12.5∼20Hz, at 25 It is smaller than the section of ordinary track bed within ∼1000Hz. (2) The maximum Z-vibration level measured from the tunnel wall is most suitable for evaluating the seismic source intensity of the subway, and the seismic source intensity of the subway line is 65.69 dB.